The Relationship Between the Philosophy of Mathematics and Culture-Based Learning Models - Lois Tambunan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Philosophy and mathematics have a relationship in the teaching of mathematics, which can be seen in the mathematics learning models, especially those based on constructivism and culture. The purpose of this study is to provide an in-depth review of the philosophy of mathematics, the mathematics learning model reviewed from the perspective of educational philosophy, as well as to examine various references related to philosophy, philosophy of education, philosophy of mathematics, mathematics learning models related to philosophy, and the philosophy of mathematics in relation to culture-based learning models. Data collection techniques use secondary data from books, articles, or other reading materials that support this research. This research method is a literature study with a qualitative approach. The data analysis technique emphasizes references or literature from various studies on philosophy, philosophy of education, philosophy of mathematics, mathematics learning models related to philosophy, and the philosophy of mathematics related to culture-based learning models. The results of the discussion in this paper conclude that: 1) The philosophy of mathematics has a significant influence on mathematics learning; 2) The integration of culture into the learning model greatly supports the learning process, making it more engaging, sparking students' interest in learning, improving mathematical abilities, increasing students' motivation to learn, and making learning more practical, effective, and efficient. The usefulness of this research for others is to provide information and knowledge related to the philosophy of mathematics to culture-based mathematics learning models.